Looking for the Elusive Imine Tautomer of Creatinine: Different States of Aggregation Studied by Quantum Chemistry and Molecular Spectroscopy. Issue 10 (13th July 2021) - Léon, Iker; Tasinato, Nicola; Spada, Lorenzo; Alonso, Elena R.; Mata, Santiago; Balbi, Alice; Puzzarini, Cristina; Alonso, Jose L.; Barone, Vincenzo
Abstract: New spectroscopic experiments and state‐of‐the‐art quantum‐chemical computations of creatinine in different aggregation states unequivocally unveiled a significant tuning of tautomeric equilibrium by the environment: from the exclusive presence of the amine tautomer in the solid state and aqueous solution to a mixture of amine and imine tautomers in the gas phase. Quantum‐chemical calculations predict the amine species as the most stable tautomer by about 30 kJ mol −1 in condensed phases. On the contrary, moving to the isolated forms, both Z and E imine isomers become more stable by about 7 kJ mol −1 . Since the imine isomers and one amine tautomer are separated by significant energy barriers, all of them should be present in the gas phase. This prediction has indeed been confirmed by high‐resolution rotational spectroscopy, which provides the first experimental characterization of the elusive imine tautomer. The interpretation of the complicated hyperfine structure of the rotational spectrum, originated by three 14 N nuclei, makes it possible to use the spectral signatures as a sort of fingerprint for each individual tautomer in the complex sample. Abstract : A journey among the aggregation states of a key biomolecule, creatinine, is reported, guided by state‐of‐the‐art quantum‐chemical computations and spectroscopic techniques. The fine tuning of the creatinine tautomeric equilibrium by different environments is unveiled and fully understood by vis‐à‐vis comparison between simulated and experimental signatures.